INVERTER 3 kVA SATU FASE DENGAN METODE DIRECT DIGITAL SYNTHESIS MENGGUNAKAN 16-BIT DIGITAL SIGNAL CONTROLLER UNTUK INTEGRASI DENGAN JARINGAN DISTRIBUSI 220 V rms - , Yohan Fajar Sidik ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The recent demand of renewable energy elevates rapidly. Inverter as one equipment relates closely to the renewable energy sector gain more and more important role by this condition. In a grid-connected system, the inverter should be able to adjust its output voltage and frequency in synchronize with the grid. The issues related to this is the output voltage and frequency resolution. Normally, in order to be able to control its output parameters, an inverter employs specific switching strategies such as sinusoidal pulse width modulation (SPWM). In this research, a direct digital synthesis (DDS) is proposed in order to create sinusoidal pulse width modulation (SWPM) that can meet the synchronization requirements such as voltage and frequency. The DDS is digitally implemented using low cost 16-bit digital signal controller. DDS is a technique to create various signal based on lookup table. The ability to adjust its frequency output since using a counter as an address to take some data form table. Meanwhile, the voltage adjustment is obtained by multiplying the data from table with decimal in range 0 - 1. A prototype has been built in the lab scale to verify the proposed system design. Experiment results has shown that the voltage ranges of 47,2 - 246 V and frequency resolution of 1 Hz can be achieved through the low cost controller. Another result, the efficiency of inverter is above 82 %.